Correlation between Understanding about Nature of Science and Orientation to Teaching Science: An Exploratory Study with Thai First-Year Preservice Biology Teachers - Luecha Ladachart (Journal of Education in Science, Environment and Health)
Research in teacher education has given increasing attention to pedagogical content knowledge (PCK) as a theoretical construct that describes necessary knowledge for teachers to teach specific content. This research study aims to examine whether an understanding about the nature of science (NOS) correlates with orientation to teaching science (OTS), which is an overarching component of PCK for teaching science. Nineteen first-year preservice biology teachers completed adapted versions of an open-ended questionnaire called V-NOS and a multiple-choice OTS test called POSST whose data were transformed and then analyzed using Pearson‘s correlation. The results reveal a slightly negative correlation between these two variables, which is not statistically significant (r = −.227, p = .351). This result suggests that understanding of the NOS may not be a dimension of OTSs, so facilitating understanding of the NOS may not necessarily lead to inquiry-based OTSs.